Cell immobilization strategies for biotransformations - Lapponi, M. J.; Méndez, M. B.; Trelles, J. A.; Rivero, C. W
This review deals with up-to-date applications related to cell immobilization used for varied biocatalytic purposes in diverse areas ranging from the food and dairy industry, synthesis of added value products such as biopharmaceuticals, bioplastics, additives, or biofuels, bioremediation, and development of biological biosensors to tissue regeneration in the medical area. These diverse applications have been achieved by different immobilization methodologies such as entrapment, encapsulation, adhesion, covalent, or mixed. Finally, it is well established that cell immobilization or restriction within a matrix or supports allows improving biocatalyst stability, reusability, mechanical resistance, reduces bioprocess costs, and represents a basic requirement for industrial application. The methods used for cell immobilization in different areas of biocatalysis in the last two years are summarized.
Keywords: WHOLE CELLS; ENTRAPMENT; ALGINATE; BIOCATALYSIS